Involvement of platelets in extrahepatic metastasis of hepatocellular carcinoma. Issue 14 (25th March 2014) - Morimoto, Yuki; Nouso, Kazuhiro; Wada, Nozomu; Takeuchi, Yasuto; Kinugasa, Hideaki; Miyahara, Koji; Yasunaka, Tetsuya; Kuwaki, Kenji; Onishi, Hideki; Ikeda, Fusao; Miyake, Yasuhiro; Nakamura, Shinichiro; et al.
<x xml:space="preserve">Abstract</x> Aim Recently, a relationship between platelets and cancer metastasis has been reported. The aim of this study is to elucidate the risk factors for extrahepatic metastasis (EHM), with emphasis on association with platelets in patients, with hepatocellular carcinoma (HCC). Methods We examined risk factors for EHM in 1613 consecutive, newly diagnosed HCC patients by logistic regression analysis (case–control study). We also examined the factors by Cox proportional hazard model in a retrospective cohort fashion in 803 patients who received non‐curative treatment for HCC. Results In the case–control study, multivariate analysis revealed that high platelet counts (odds ratio [OR] = 4.84; 95% confidence interval [CI] = 1.29–29.54; P = 0.01), high tumor number and the presence of macroscopic vascular invasion were significantly associated with EHM. In the cohort study, EHM was diagnosed in 71 patients during the study period (mean observation time = 23.3 months). On multivariate analysis, high tumor number, high des‐γ‐carboxyprothrombin (DCP) and Child–Pugh class A were significantly correlated with EHM, and the patients with high platelet counts tended to develop EHM (OR = 1.73; 95% CI = 0.99–3.14; P = 0.055). Conclusion HCC patients with high platelet counts, as well as large numbers of tumors, high serum DCP and Child–Pugh class A, are at risk for EHM.